BUMN, MSMEs and Development Disparity in Jember, Banyuwangi, Bondowoso and Lumajang Districts - Yusron Rozzaid; Bayu Wijayantini; Nurul Qomariah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
This study aims to analyze the existence of state-owned Perum Perhutani land, PT Perkebunan Nusantara XII and the role of MSMEs and their relation to welfare and development disparities. The analytical method used is descriptive analysis using the Williamson index. While presenting the data in the form of maps using ArcGIS, quadrant analysis, and explanatory using Pearson correlation and path analysis. The results showed that high disparities occurred in Jember Regency with an IW of (0.73). Low disparities occur in Lumajang (0.20), Bondowoso (0.24) and Banyuwangi (0.25). The results of the covariance-based Structural Equation Model (SEM) in the form of path analysis with AMOS software obtained a model where MSMEs are in the trade, hotel, restaurant sector; MSMEs in the Financial Services sector have a direct positive and significant effect on per capita income with a path coefficient of 0.3 each. The existence and area of land have a negative and significant effect with a path coefficient of -0.77. MSME service sector has a significant indirect effect on income per capita. Based on the findings, the local government needs to invite PTPN XII to participate in development that has a direct impact on the welfare of the community around the land, through the development of natural potential and land for tourism purposes which is supported by the development of MSME products for the local community.